Media Education as an Effective Perspective on the Formation of Ideology in Society Through the Influence of Self-Consciousness - Melnykova-Kurhanova, O.; Bella, M.; Naumenko, L.; Ostrovska, N.; Liashchenko, A.; Murzina, O. A.; Мурзіна, Олена Анатоліївна (My University, 2022)
The study identifies the trends of media education in the post-industrial period, marked by the development of information and communication technologies in the integration and globalization processes. Society needs competent specialists who develop and strive for self-realization in society. The educational process is a phenomenon that covers different spheres of human activity and determines the main aspects of the regulatory and legal framework. The article illustrates innovative styles of media education that are an effective perspective on the formation of ideology in society through the influence of self-consciousness in educational activities. In order to identify the main aspects of media technology in the educational process, we investigated the basic methodological and theoretical foundations based on the generalizations of researchers and scientists. The meaning of the concept of media education and media technology was studied, the evolution of education from the introduction of information and communication technologies in the learning process to the formation of critical thinking and analysis of the information space was investigated. The method of synthesis, analysis was used to define the main concepts of the study. Descriptive method, research and scientific method was used to compile and summarize the results of the implementation of media education as a prospect for the formation of ideology in society through the influence of self-consciousness.
Keywords: informatization of society; critical thinking; media worldview; information and communication technologies